2017
DOI: 10.1097/md.0000000000007480
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intraoperative dexmedetomidine on acute kidney injury after pediatric congenital heart surgery

Abstract: Background:Dexmedetomidine has been reported to have a renal protective effect after adult open heart surgery. The authors hypothesized that intraoperative infusion of dexmedetomidine would attenuate the decrease in renal function after pediatric open heart surgery.Methods:Twenty-nine pediatric patients (1–6 years) scheduled for atrial or ventricular septal defect repair were randomly assigned to receive either continuous infusion of normal saline (control group, n = 14) or dexmedetomidine (a bolus dose of 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 30 publications
0
39
1
Order By: Relevance
“…Five studies were excluded for several reasons including the lack of primary outcomes, evaluation of noncardiac surgery, and the lack of a control group. Eventually, 9 studies comprising 4 RCTs, 1 quasi‐RCT and 4 observational cohort studies ultimately met our selection criteria and were included in the quantitative synthesis. Among them, 7 studies were pooled for JET, and 2 studies were pooled for AKI .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies were excluded for several reasons including the lack of primary outcomes, evaluation of noncardiac surgery, and the lack of a control group. Eventually, 9 studies comprising 4 RCTs, 1 quasi‐RCT and 4 observational cohort studies ultimately met our selection criteria and were included in the quantitative synthesis. Among them, 7 studies were pooled for JET, and 2 studies were pooled for AKI .…”
Section: Resultsmentioning
confidence: 99%
“…Based on our literature review, there are two studies including 1RCT and 1 retrospective study that have assessed the efficacy of dexmedetomidine in the prevention of pediatric cardiac surgery associated AKI . Positive renoprotective effects were reported in these two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Prospective studies in cardiac surgery are sparse and rather small. 65 Together, available data on the efficacy of sympatholytic drugs added peri-operatively to the patients' medications in clinical scenarios where renal ischaemia and sympathetic activation likely contribute to AKI are ambiguous. 64 A single-centre study in 30 paediatric patients (1-6 years old) who underwent cardiac surgery reported lower GFR and higher AKI incidence based on serum creatinine measurements obtained 5 minutes and 2 hours after weaning from cardiopulmonary bypass.…”
Section: Of 10mentioning
confidence: 99%
“…64 A single-centre study in 30 paediatric patients (1-6 years old) who underwent cardiac surgery reported lower GFR and higher AKI incidence based on serum creatinine measurements obtained 5 minutes and 2 hours after weaning from cardiopulmonary bypass. 65 Together, available data on the efficacy of sympatholytic drugs added peri-operatively to the patients' medications in clinical scenarios where renal ischaemia and sympathetic activation likely contribute to AKI are ambiguous. In contrast to experimental renal IR studies where conditions can be well standardized, the effects of sympatholytics may have been blurred by the complexity of clinical scenarios and factors such as patient age, genetic diversity, associated chronic diseases and diverse co-medications.…”
Section: Clinical Akimentioning
confidence: 99%